Possible light-induced superconductivity in metallic K3C60 - Cantaluppi, A; Mitrano, M; Nicoletti, D; Kaiser, S; Perucchi, A; Lupi, S; Di Pietro, P; Pontiroli, D; Ricco, M; Subedi, A; Clark, S; Jaksch, D; et al. (Institute for Electrical and Electronics Engineers, 2016)
We report possible light-induced superconductivity in the organic molecular solid K3C60, a superconductor at equilibrium below Tc=20 K. In our experiment we excited this alkali-doped fulleride with strong femtosecond pulses, tuned to be resonant with local molecular vibrational modes. By means of THz time-domain spectroscopy, we detected the pump-induced changes in the conductivity spectrum as a function of pump-probe time delay. Strikingly, at temperatures up to 100 K, we measured a light-induced response with the same optical properties of the equilibrium superconductor. An interpretation in terms of non-linear coupling between different vibrational modes may give hints to explain this emergent physics away of equilibrium.